ANALYSIS OF SURPLUS-DEFICIT IRRIGATION WATER PAMUKKULU TAKALAR REGENCY, SOUTH SULAWESI - Sitti Nur Farida (The University of Lampung, 2014)
Irrigation areas with specific technical, will have acertain pattern as well and irrigation water available isinfluenced by the condition of water resources and management, The successin the management of irrigationwater is determined by the balance of irrigationwater available andthe requiredwater. This researchwas carriedout by predicting potentialwater resources useWatershedModeling System, calculate cropwater requirements todetermine the surplus-deficit water. The results were obtained monthly discharge based predictionWMS 1,32-24,7 m3/sec, which the lowest discharge in September and the highest in February. Crop water requirements,shortage ofwaterf or 7months (May-November). Utilization of the damme driverwater at the weir Pamukkulucan supply these needs, with a surplus of water, 0,1-3,85m3/sec/month.